The effect of supported realistic mathematics education with short films on conceptual and procedural knowledge - GUN SAHIN, Zuhal; GURBUZ, Ramazan (Acta Didactica Napocensia, 2022)
In Realistic Mathematics Education (RME), students should reach formal mathematics knowledge and explore mathematics based on their informal knowledge. The problems chosen in the exploration process should apply mathematics to real-life situations and be suitable for students to explore and create mathematical structures. In the current study, the researchers presented real life problem situations with short films for getting students' attention, showing a mathematical subject in daily life, and increasing the effect of problems. In this manner, the purpose of this study was to the effects of enriched realistic mathematic education with short films on students' conceptual and procedural knowledge. Also, the researchers received participants' opinions about the teaching process. Therefore, the researchers selected 10 students as participants, who continued the 7th grade, and they examined the subject of "Equality and Equations." For collecting data in this study, the researchers used worksheets, interviews, and study journals, and they used content analysis for analyzing the data. The result of the study showed that this teaching method affected the conceptual and procedural knowledge of the students positively, and they discovered with pleasure mathematics.